Italian health workers' knowledge, attitudes and behaviours towards COVID-19 vaccination. (20th October 2021) - Regazzi, L; Paladini, A; Marziali, E; Lontano, A; Calabrò, G E; Messina, R; Laurenti, P; Boccia, S; Ricciardi, W; Cadeddu, C
Abstract: Background: Vaccine hesitancy is the reluctance or refusal to be vaccinated. While it has been widely studied for various contagious diseases, there is still a lack of knowledge about this phenomenon for COVID-19, especially if health workers' hesitancy is considered. Methods: An extensive review of the literature was conducted to identify the main determinants of vaccine hesitancy in health workers, as well as to find already validated surveys to evaluate the knowledge, attitudes and behaviors (KAB) of health workers towards vaccination, both in general and with specific regard to COVID-19. Building on the available information, a new survey was developed to assess the KAB of Italian health care workers towards COVID-19 vaccination after validation with a pilot study in a diverse sample of 30 Italian health workers. Results: A new survey was validated to assess the KAB of health workers towards COVID-19 vaccination in Italian health workers. The survey requires about 6 minutes to complete and is composed of 30 questions, investigating different domains: socio-demographic and professional characteristics (6); health status (2); attitudes (11); behaviors (6); knowledge (4). The survey will be administered to a representative sample of at least 385 Italian health workers through the web platform SurveyMonkey in the period June-September 2021. Preliminary results will be available by the end of October 2021. Conclusions: By analyzing KAB towards COVID-19 vaccination with a new tool, the magnitude and determinants of health worker's COVID-19 vaccine hesitancy will be evaluated to understand how to improve health workers' perception towards COVID-19 vaccination and, consequently, foster their positive influence on the general population. Key messages: We explore the knowledge, attitudes and behaviors towards COVID-19 vaccination in all categories of health workers operating on the Italian territory to understand the reasons of vaccine hesitancy. Understanding the determinants of COVID-19 vaccine hesitancy in Italian health workers is necessary given their influence on the perception of the general population in Italy.